Cisplatin Ototoxicity: Examination of the Impact of Dosing, Infusion Times, and Schedules In Pediatric Cancer Patients - Camet, Miranda L.; Spence, Anne; Hayashi, Susan S.; Wu, Ningying; Henry, Jennifer; Sauerburger, Kara; Hayashi, Robert J. (Frontiers in Oncology, 2021)
Background Sensorineural hearing loss is a well-known side effect of cisplatin (CDDP). There is limited research on the effect of dosing, infusion times, and schedules of cisplatin administration and their impact on hearing loss. Methods A retrospective review of 993 pediatric patients’ medical and audiological charts from August 1990 to March 2015 was conducted using stringent inclusion criteria to characterize patients with hearing loss. 248 of these patients received CDDP. Of these, 216 patients had sufficient CDDP infusion data to assess for sensorineural hearing loss attributable to CDDP and its associated risk factors. Chart reviews were performed to extract clinical data including CDDP dosing information. Demographic and clinical characteristics were summarized by descriptive statistics, and univariate and multivariate logistic regressions were performed to examine the relationship between hearing loss and specific parameters of cisplatin administration (amount infused per dose, prescribed infusion time, total number of doses, number of doses per cycle, number of cycles, cumulative cisplatin exposure). Stepwise variable selection procedure was performed in the multivariate model building to extract the best subset of risk factors for the prediction of hearing loss and worsening ototoxicity grade using an established ototoxicity grading scale from the International Society of Pediatric Oncology (SIOP). Results A total of 153 patients with complete medical and audiologic data were evaluable for analysis. Hearing loss was identified in 72.6% of the patients. Multivariate analysis revealed that age [OR=0.90 (0.84-0.97), p-value=0.0086], radiation to any part of the body, [OR=3.20 (1.29-7.93), p-value=0.012], amount infused per dose (mg/m2) [OR=1.018 (1.002-1.033), p-value=0.029], and cumulative cisplatin exposure (mg/m 2) [OR=1.004 (1-1.008), p-value=0.027] were associated with hearing loss. Similar associations were also found between these risk factors and worsening SIOP grade. Conclusion In one of the largest studies examining the influence of CDDP dosing and schedules on hearing loss, we found the amount of CDDP infused per dose is a significant risk factor. Considerations in designing regimens that reduce the amount of CDDP infused per dose may reduce the risk of hearing loss. Randomized prospective trials are needed.